2022
DOI: 10.3389/fgene.2022.991706
|View full text |Cite
|
Sign up to set email alerts
|

A gene expression signature in HER2+ breast cancer patients related to neoadjuvant chemotherapy resistance, overall survival, and disease-free survival

Abstract: Breast cancer ranks first in terms of mortality and incidence rates worldwide among women. The HER2+ molecular subtype is one of the most aggressive subtypes; its treatment includes neoadjuvant chemotherapy and the use of a HER2 antibody. Some patients develop resistance despite positive results obtained using this therapeutic strategy. Objective. To identify prognostic markers for treatment and survival in HER2+ patients. Methods. Patients treated with neoadjuvant chemotherapy were assigned to sensitive and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
(65 reference statements)
0
2
0
Order By: Relevance
“… 7 In addition, it has been suggested that DIRAS1 is a good predictor of overall survival in HER2+ breast cancer patients receiving neoadjuvant chemotherapy. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 7 In addition, it has been suggested that DIRAS1 is a good predictor of overall survival in HER2+ breast cancer patients receiving neoadjuvant chemotherapy. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that downregulation of BCL2 correlates with improved disease-free survival (DFS) in breast cancer patients [ 31 ]. Additionally, the upregulation of ATF6B expression has been linked to favorable DFS outcomes [ 32 ]. Additionally, elevated PLA2G16 gene expression has been correlated with improved DFS, consistent with findings in the literature [ 33 ].…”
Section: Discussionmentioning
confidence: 99%